A Hybrid Reasoning Model for "Whole and Part" Cardinal Direction Relations. (28th February 2013) - Kor, Ah-Lian; Bennett, Brandon
Abstract : We have shown how the nine tiles in the projection-based model for cardinal directions can be partitioned into sets based on horizontal and vertical constraints (called Horizontal and Vertical Constraints Model ) in our previous papers (Kor and Bennett, 2003 and 2010). In order to come up with an expressive hybrid model for direction relations between two-dimensional single-piece regions (without holes), we integrate the well-known RCC-8 model with the above-mentioned model. From this expressive hybrid model, we derive 8 basic binary relations and 13 feasible as well as jointly exhaustive relations for the x - and y -directions, respectively. Based on these basic binary relations, we derive two separate 8 × 8 composition tables for both the expressive and weak direction relations. We introduce a formula that can be used for the computation of the composition of expressive and weak direction relations between "whole or part" regions. Lastly, we also show how the expressive hybrid model can be used to make several existential inferences that are not possible for existing models.